Relaxin-2 Expression in Oral Squamous Cell Carcinoma. Issue 3 (July 2016) - Marioni, Gino; Di Carlo, Roberto; Ottaviano, Giancarlo; Cappellesso, Rocco; Bedogni, Alberto; Marchese-Ragona, Rosario; Stritoni, Paola; Rossi, Marco; Zanoletti, Elisabetta; Favaretto, Niccolò; Valentini, Elisa; Apolloni, Federico; et al.
Background: When advanced, oral squamous cell carcinoma (OSCC) may involve adjacent non-epithelial structures, and the prognosis is worse for bone invasion. Human relaxin-2 is a peptide hormone that has recently been associated with cancer. It can induce human osteoclast differentiation and activation, suggesting a role in tumor-driven osteolysis. This study was a preliminary assessment of the prognostic role of relaxin-2 in surgical specimens of OSCC tissue and adjacent but uninvolved mandibular/maxillary bone. Methods: Relaxin-2 immunohistochemical expression and reaction intensity were assessed in tumor and uninvolved adjacent mandibular/maxillary bone specimens from 23 operated OSCC patients. Results: All OSCC specimens were positive for relaxin-2. The intensity of its reaction in OSCC correlated significantly with the pattern of the tumor's invasion front (p = 0.02), being higher with the infiltrative pattern. Mean relaxin-2 immunohistochemical expression was higher in patients whose OSCC recurred after treatment than those experiencing no recurrence (81.3% ± 22.6% vs. 59.5% ± 29.7%, respectively). A significant direct association emerged between relaxin-2 expression in OSCC specimens and recurrence rate (p = 0.049). Conclusions: Relaxin-2 expression in OSCC should be further investigated as a potentially useful marker for identifying patients at higher risk of recurrence, who might benefit from closer follow-up and more aggressive adjuvant therapy. In other oncological settings, increasing evidence of relaxin being produced by cancer cells is prompting efforts to synthesize human relaxin-2 analogs capable of acting as antagonists and limiting tumor growth.